COMPARATIVE LITERARY STUDY ON MOCHTAR LUBIS’ HARIMAU HARIMAU AND HERMAN MELVILLE’S MOBY DICK - ANDAYANI, AMBAR; JUPRIONO, D. (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
There are two tendencies in comparative literary study. First, in comparative literary study, both of literatures from two countries are compared for certain points (theme, stylistic, setting, characterization, etc). Second, comparative literary study raises literary critical appreciation from other discipline perspectives (psychology, sociology, philosophy, religion, anthropology, politic). In this article, both tendencies are applied at once. The focus of this paper is about the theme in novels Harimau Harimau Muchtar Lubis and Moby Dick Herman Melville. It uses existentialism philosophical approach and criticism literature. The finding of the research, if we compare them, the existentialism theme in Harimau Harimau and Moby Dick has similarities that human being has freedom to determine her/his choice in her/his life for the future. Yet, what choice that she/he takes, it has a risk that she/he must face with responsibility as a human being. The pursuits of the responsibility caused anxiety, frightened, suffering as what the characters face in these novels. Key words: comparative literature, existentialism, theme, choice of life, causality law